2007
DOI: 10.3182/20070820-3-us-2918.00028
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Models of Engine Hc Emissions, Exhaust Temperature and Catalyst Temperature for Automotive Coldstart

Abstract: The initial 1-2 minutes of operation of an automotive spark-ignition engine, commonly called as the "coldstart" period, produces more than 75-80 % of the hydrocarbon (HC) emissions in a typical drive cycle. Model-based controller development requires accurate, yet simple, models that can run in realtime. Simple, intuitive models are developed to predict both tailpipe hydrocarbon (HC) emissions and exhaust temperature during coldstart. Each of the models is chosen to be sum of first order linear systems based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In the case of spark ignited (SI) engines, exhaust temperature for higher loads lies in the region of 600 °C, and in some cases, may even reach 900 °C, while at idle, it lies in the region of 300 °C, [22], and according Zavala et al [18], engine speed has a The PI controller uses the set speed N set and the actual speed N to set the value of the control variable volumetric efficiency η vp . The physical limits of the system are defined by a saturation filter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of spark ignited (SI) engines, exhaust temperature for higher loads lies in the region of 600 °C, and in some cases, may even reach 900 °C, while at idle, it lies in the region of 300 °C, [22], and according Zavala et al [18], engine speed has a The PI controller uses the set speed N set and the actual speed N to set the value of the control variable volumetric efficiency η vp . The physical limits of the system are defined by a saturation filter.…”
mentioning
confidence: 99%
“…In the case of spark ignited (SI) engines, exhaust temperature Energies 2017, 10,1948 4 of 14 for higher loads lies in the region of 600 • C, and in some cases, may even reach 900 • C, while at idle, it lies in the region of 300 • C, [22], and according Zavala et al [18], engine speed has a stronger influence than the air mass inlet rate on exhaust temperature. At the time of this writing, the most relevant study on the behaviour of the exhaust temperature of SI engines has been found to have been conducted by Eriksson [23], who based on results from crank angle based combustion models assumed a linear dependence of the exhaust temperature on the exhaust mass flow rate.…”
mentioning
confidence: 99%
“…8, the observer needs data for turbine pressure and temperature. These data are either estimated [22,23] The new turbine model is applied to the observer in Fig.8. Performance of the observer is evaluated in terms of stability and accuracy by changing the engine working conditions.…”
Section: Turbocharger Nonlinear Observermentioning
confidence: 99%
“…Thus, other than the accuracy and complexity of the model, there is another important element, namely flexibility or the capability of being retrained over the working cycle of the ICE system, which should be taken into account. By using an identifier (observer) which can retain its accuracy over the entire working cycle, it is possible to develop efficient closed-loop engine coldstart controllers which, in turn, can gratify the stringent legislative regulations targeting the low level tailpipe emissions of unburned HCs [10].…”
Section: Introductionmentioning
confidence: 99%